2021
DOI: 10.1109/jphot.2021.3054914
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Light-Extraction Efficiency of Flip-Chip AlGaN-Based Deep-Ultraviolet Light-Emitting Diodes Adopting AlGaN Metasurface

Abstract: Herein, we investigate the influence of an AlGaN metasurface on AlGaN-based deep-ultraviolet light-emitting diodes' lightextraction efficiency by utilizing the 3D finite-difference time-domain method. As the first step in this study, we optimize an AlGaN metasurface to maximize the transmittance from LED to air. Then, six different flip-chip structures' light-extraction efficiencies are compared with each other to judge the usefulness of the metasurface's adoption on AlGaN-based LED. Considered structures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The LEEs of DUV‐LED with unstructured plate are 3.34% and 0.48% for TE and TM modes, fitting well with the previous works. [ 36,39 ] By etching optimized PCEL on the n‐AlGaN surface, the LEEs rise to 9.37% and 2.1% respectively for the TE and TM modes, indicating the corresponding improvement as 181% and 337%, respectively. As expected, the LEEs of PCEL are quite similar with Meta‐I, especially for the TE mode (the deviation is 1.7%), indicating the superiority of functional reconfiguration by metasurface.…”
Section: Lee Improvement Of Duv‐ledmentioning
confidence: 99%
See 2 more Smart Citations
“…The LEEs of DUV‐LED with unstructured plate are 3.34% and 0.48% for TE and TM modes, fitting well with the previous works. [ 36,39 ] By etching optimized PCEL on the n‐AlGaN surface, the LEEs rise to 9.37% and 2.1% respectively for the TE and TM modes, indicating the corresponding improvement as 181% and 337%, respectively. As expected, the LEEs of PCEL are quite similar with Meta‐I, especially for the TE mode (the deviation is 1.7%), indicating the superiority of functional reconfiguration by metasurface.…”
Section: Lee Improvement Of Duv‐ledmentioning
confidence: 99%
“…The frequently used flip-chip LED structure [36,37] is adopted to investigate the LEE enhancement, as shown in Figure 4a. As the TIR exists extensively at the interface between the dielectrics with different refractive indices, the substrate-free AlGaN-based structure with thin epitaxial layers is selected to accelerate the simulation process.…”
Section: Lee Improvement Of Duv-ledmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the quantum barrier and electron barrier layer (EBL) can effectively confine carriers in the active region, there are still a part of energetic carriers escaping from multiple quantum wells (MQWs) to p-doped layer in the form of thermionic overflow or defect-related tunneling process [12][13][14]. In addition, previous works also reported that a variety of factors, such as extended dislocations (EDs), quantum confined stark effect, carrier delocalization, and Auger recombination, also affected the efficiency droops of AlGaN-based UVC-LEDs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Yang Peng employed this encapsulation material doped with fluoropolymer on an aluminum nitride substrate to enhance the LEE of a chip-on-board encapsulation structure [ 28 ]. Joosun Yun and Hideki Hirayama proposed different wafer structures in a comparative study with six different flip-chip structures, obtaining an AlGaN meta-surface for improved LEE [ 29 ].…”
Section: Introductionmentioning
confidence: 99%